STAKEHOLDERS’ PERSPECTIVES ON PROFESSIONAL COMPETENCIES OF ARCHITECTS IN NIGERIA: A CASE FOR CURRICULUM REVIEW - Adewale, Peter Oluwatoyin; Siyanbola, Ahmid Bukola; Adedeji, Afolabi Idowu (Journal of Architectural Research and Education, 2021)
This paper examined the broad evidenced-based view of all stakeholders in the architectural profession on the knowledge, skills and attributes expected of architects in Nigeria with a view to identifying the major industry-relevant competencies necessary for the profession. Structured questionnaire was used to elicit information from practising architects, allied building professionals and contractors. Data were analysed using Relative Importance Index and Kruskal-Wallis test. Results revealed that computer-aided design skills and knowledge of sustainable design are the foremost significant new competencies required of architects in Nigeria. The paper concludes that architectural education curriculum needs to be reviewed to include these skills.